Increase in growth and biomass in Phaseolus vulgaris L. seedlings cultivated in biodegradable vases (Research, Society and Development, 2020)
The green coconut (Cocos nucifera) is one of the most consumed fruits on the Brazilian coast, but it’s use generates an excess of waste that is improperly discarded by consumers. The biomass produced by the disposal of coconut is a potential input for making sustainable products. With this, the present work had as objective to use the coconut mesocarp in the making of biodegradable jars. In this way, the heating of the 5% starch solution was carried out by mixing the fragmented coconut mesocarp, serving as raw material for the production of the biodegradable ecological jug. After production, the jug was used for the cultivation of Phaseolus vulgaris L. seeds and the seed germination rate, height, number of leaves, seedling biomass and soluble sugar contente of the seedlings grown in biodegradable jars annd jars of polyethylene. As a results, it can be seen that seedlings grown in biodegradable jars, after 21 days of sowing, they had a significant increase in their height, number of leaves and biomass, when compared to the seedlings growing in polyethylene jars. Thus, it can be observed that the work proposes and excellent use to avoid the waste of the coconut mesocarp, providing a sustainable alternative to the use of plastic and an improvement in the cultivation of Phaseolus vulgaris L. seedlings.